The Ross classification as a tool for nursing evaluation in pediatric patient with heart disease. - Gatti, Chiara; Bardeggia, Valentina; Borgognoni, Cinzia; Bianco, Francesco; Guerra, Federico (Journal of Biomedical Practitioners, 2023)
Background Heart failure is a clinical syndrome following myocardial dysfunction with inadequate response to the body’s metabolic demands. It appears more critical and complex in children than in adults. It is essential to treat this condition early: for this reason, the Ross classification was developed, which assigns a score to the patient based on the presented signs and symptoms. Aims The primary aim was to evaluate whether the data (signs, symptoms and behaviors of the child) collected non-invasively by the nurse were predictive of the risk of heart failure according to the Ross Classification in a cohort of pediatric patients after cardiac surgery for correction of atrial septal defect (ASD) or ventricular septal defect (VSD). The secondary aim was to correlate the trend of the scores obtained from the classification with variables such as hospitalization time (in days) and number of rehospitalizations. Methods Retrospective observational study conducted on a sample of medical and nursing records of patients between 0 and 18 years hospitalized at the Congenital Pediatric Cardiology and Heart Surgery - Pediatric Intensive Care Unit of Azienda Ospedaliero Universitaria delle Marche in 2021. A score was assigned according to the Ross Classification to each patient. A statistical analysis followed using Wizard and STATA software. Results Most of the patients belonged to the second class of Ross (51%), while none presented parameters included in the fourth class. It emerged that patients included in the second and third classes of Ross had a longer hospital stay than those who were included in the first class as well as a greater relative risk of total hospital stay. Hospitalizations involved 5% of the sample (3/57). Conclusions Nurse is fundamental in the detection of the parameters for the computation of the Ross classification in heart failure in pediatrics. In addition to the clinical-instrumental data, observation during feeding and the severity of the related respiratory distress is fundamental. The creation of a multidisciplinary team that addresses every aspect related to heart failure allows an effective comparison between different health professionals and an excellent level of assistance.